Analysis Of Zakat Distribution Policy At Baitul Mal In Central Aceh Regency - Amelia, Tri Karunia Putri; Anwar, Saiful (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
The policy of the Baitul Mal in Central Aceh Regency regarding zakat distribution aims to combat poverty in the medium to long term. Collected zakat funds are managed organizationally by the Baitul Mal, emphasizing transparency and accountability. The study investigates zakat distribution programs, related policies, and challenges the Baitul Mal faces. It employs a qualitative approach to provide a scientific overview. Results are expected to show alignment with Quranic mandates, ensuring independent, transparent, and accountable practices. The research aims to depict the reality of zakat distribution policies as efforts to alleviate poverty, catering to recipients' needs (Mustahiq) through consumptive or productive means.